(untitled) (Research, Society and Development, 2018)
While survival is one of the most acclaimed genres of Steam users, there is still criticism that it shows discontent that survival games are not really about survival. In view of the above, the objective of this is to analyze the survival games of Steam and present the qualitative characteristics for the development of games of this genre, in order to highlight the fundamental aspects to be considered when designing a game. Within the identified issues are: simulation, gameplay, difficulty, ambiance and graph. These were identified from the user-driven (player) analyzes of 15 survival games contained on Steam. The analysis will point the way for developers to approach survival mechanics systematically, but not rigidly. It was elaborated based on successful games of the same genre, and aims to emphasize the importance of the five components as methodology for development of survival games.